[OP.2B.08] POOR MEDICATION ADHERENCE IN THE RELATIONSHIP BETWEEN ANTIHYPERTENSIVE MEDICATION AND FALLS: A PROSPECTIVE COHORT STUDY OF OLDER ADULTS. (September 2017) - Dillon, P.; Smith, S.; Gallagher, P.; Cousins, G.
Abstract : Objective: There is on-going debate as to whether antihypertensive medications are associated with an increased falls risk in older adults. Patients initiating antihypertensive treatment have been observed to have an increased risk of falling; however studies of long-term users of antihypertensive medication have reported conflicting findings. One factor that has not been measured in published studies of prevalent antihypertensive users is adherence. Patients with non-adherence behaviour may be repeatedly exposed to an increased fall risk similar to initial antihypertensive use. Our objective was to investigate the longitudinal association between poor adherence to antihypertensive medication and falls in older adults (>65 years). Design and method: Community dwelling older adults (N = 1592) recruited from 106 community pharmacies in the Republic of Ireland between March and May 2014 completed a baseline structured telephone interview and a follow-up structured telephone interview at 12 months, which were linked to dispensing records for the previous 12 months. To assess the longitudinal association between adherence to antihypertensive medication and falls, adherence was estimated (as the number of 5 day gaps in medication supply) from linked dispensing records for the 12 month period prior to the baseline interview and falls were assessed via questionnaire for the 12 month period prior to the follow-up interview. Results: Adjusting for demographics, co-morbidities and medication history, poor adherence to antihypertensive medication was associated with an increased risk of falls (aRR 1.11, 95% CI 1.03–1.19, p = 0.005), injurious falls (aRR 1.19, 95% CI 1.06–1.33, p = 0.003) and a greater number of falls (aIRR 1.15, 95% CI 1.04–1.27, p = 0.006) during 12 month follow-up (n = 1084). Conclusions: In older adults, periods of non-adherence to antihypertensive medication may be a precipitating factor in the relationship between long-term antihypertensive medication use and falls. In reconciling the risk-benefit of continuing antihypertensive therapy in older patients at risk of falling, clinicians should be aware of this potential mechanism, which may relate to fluctuations in blood pressure secondary to non-adherence. Interventions aimed at improving adherence should be considered as part of interventions to prevent fall injury for patients being treated with antihypertensive medication.